Anak dengan Tuberkulosis (TB) Paru Kasus Baru Terkonfirmasi Bakteriologis dengan Riwayat Human Immunodeficiency Virus (HIV) yang Menjalani Pengobatan Antiretroviral (ARV) - Soemarwoto, Retno Ariza S; Afryan, I Made; Nareswari, Shinta; Sinaga, Fransisca; Saputra, Oktadoni; Herliyana, Lina; Hidayat, Hidayat (Medula, 2025)
Tuberculosis (TB) in children with Human Immunodeficiency Virus (HIV) is a complex clinical challenge due to the synergistic interaction between these two diseases, which mutually worsen the patient's clinical condition. HIV decreases immunity, thus increasing the risk of TB infection, while TB accelerates HIV progressivity. TB-HIV co-infection is a major cause of morbidity and mortality, especially in children with undetected M. Tuberculosis infection. By 2022, an estimated 710,000 HIV patients will develop TB, of which 187,000 will die. This article aims to provide an update on the management of pulmonary TB in children with HIV who are routinely on antiretroviral (ARV) treatment. The discussion covers the definition, epidemiology, etiology, disease progression, pathogenesis, diagnosis, supporting investigations, and management of TB-HIV. The diagnosis of TB in children with HIV is often difficult due to non-specific clinical manifestations and limitations of diagnostic tests. Therefore, early detection through comprehensive testing is essential. TB-HIV management requires a multidisciplinary approach, including appropriate TB treatment and integrated ARV administration. Intensive monitoring is also required to prevent complications, such as drug resistance or adverse effects of therapy. In conclusion, this article emphasizes the importance of a holistic approach in evaluating and managing pulmonary TB in children with HIV, including interprofessional collaboration, family education, and preventive efforts to improve patients' quality of life and reduce mortality.